Projecting the poleward habitat expansion of whale sharks (Rhincodon typus) in the west pacific and east Indian ocean in response to climate change - Soeon Ahn; Hyun Woo Kim; Kwang-Sik Choi; Chulhong Oh; Soo-Jin Heo; Do-Hyung Kang; Dongwha Sohn (Global Ecology and Conservation, 2025)
Climate change is accelerating the poleward redistribution of marine megafauna, including whale sharks. This study aimed to (1) identify suitable habitat beyond the whale shark’s known northern range in the Northwestern Pacific, (2) quantify projected shifts in habitat across the Western Pacific and Eastern Indian Ocean under future climate scenarios using species distribution models (SDMs), and (3) examine the influence of key environmental drivers across ecologically distinct regions using SHapley Additive exPlanations (SHAP) analysis. High-performing SDMs were developed using H2O AutoML, incorporating presence records from GBIF, OBIS, and newly documented sightings in Korean waters. The best-fitted model was hindcast (2004–2023) and forecasted for the 2050s, 2070s, and 2090s using CMIP6-based Earth System Models under three climate change scenarios. Model projections indicated substantial habitat losses in equatorial regions and concurrent poleward expansion. Predictions illuminated suitable habitat within Korean waters to 47°N under present ocean conditions, extending to nearly 50°N by the end of the century, largely due to increases in sea surface temperatures. In contrast, chlorophyll-a played a more influential role in shaping habitat suitability in the Philippines and Ningaloo Reef, indicating region-specific environmental controls. While Korean waters may emerge as a future aggregation hotspot, the Philippines are projected to experience a persistent decline in high-quality habitat, and Ningaloo Reef may undergo seasonal shifts in aggregation timing. These findings highlight the ecological importance of emerging habitats and the urgency for proactive, region-specific conservation strategies in response to climate-driven range shifts.